Perilaku Seksual Pra Nikah dan Persepsi Harga Diri Pada Mahasiswa - Wiwi Kustio Priliana (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2016)
Background: Students are teenagers who are experiencing a period of transition from childhood into adulthood during which a person is faced various challenges and problems both development and the environment. These challenges and problems have an impact on teen behavior, particularly sexual behavior. The issue of teenage sexuality is an issue that is very complex, requiring a lot of attention and resolution. Objective: To determine the perception students have high self-esteem tend to perform premarital sexual behavior of light compared to students who have a perception of low self-esteem. Methods: The study was observational using cross sectional study design (cross-sectional). Locations in Nursing Notokusumo Yogyakarta. Samples were students are 300 sample. Results: Students who have a perception of high self-esteem were more likely to light premarital sexual behavior. Perception of high self-esteem of students significantly related to the occurrence of premarital sexual behavior of light. This can be seen from the value of p = 0.001 value and the value of RP = 1.81 CI 95% = 1.41 -2.32 The analysis of the students who have high self esteem perception 69.9% of students who have high self-esteem same perception 3.69 times more likely great pre-marital sexual behavior mild compared with students who have low the perception of selfesteem. Conclusion: The relationship between the perception students have high self-esteem tend to perform premarital sexual behaviour.